Bimodal video laryngoscope assisted management of retropharyngeal abscess: a case report - Munjal, Manish; Arora, Archana; Kaur, Amanjot; Talwar, Gopika; Mirley, Rupinder; Garg, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
A retropharyngeal abscess is a suppurative collection of the deep spaces of the neck. Mostly at presentation they are massive and are a dilemma for the surgeon and the anesthetist alike, vying for space, one for therapeutic intervention and the other for airway access. Video laryngoscopic assisted evacuation of such a collection, adopting the nasopharyngeal and the transoral route was undertaken in a middle aged individual which is being reported.